IMPLEMENTASI METODE MONTESSORI DALAM MENSTIMULASI KEMAMPUAN MEMBACA PERMULAAN ANAK USIA DINI DI LOVELY BEE MONTESSORI SCHOOL MALANG - Hartono, Nurmarinda Dewi (Jurnal Penelitian Anak Usia Dini, 2023)
ABSTRACT The aims of this study were to analyze and describe (1) Montessori learning planning to stimulate early reading skills at Lovely Bee Montessori School Malang, (2) the application of the Montessori method to stimulate early childhood reading skills at Lovely Bee Montessori School Malang, and (3) evaluation of Montessori learning in stimulating early childhood reading skills at Lovely Bee Montessori School Malang. This study uses a qualitative method with a case study approach. The data collection technique used was observations, documentation, and interviews with school principal, teacher, and the Curriculum Department team. Data analysis is done by reducing data, presenting data, and drawing conclusions. Checking the validity of the data used a technical triangulation technique. The results showed that: (1) planning for Montessori learning at Lovely Bee Montessori School Malang consisted of annual planning in the form of a Montessori syllabus and Spider Web, monthly planning in the form of Lesson Plans, and daily planning in the form of Daily Lessons; (2) the application of the Montessori method in stimulating early childhood reading skills at Lovely Bee Montessori School Malang is carried out progressively and gradually through the Pink Series, Green Series, and Blue Series. The learning characteristics are using a phonics approach, prepared environment, and learning to write before reading; (3) Montessori learning evaluation consists of daily evaluations with observations and reading tests accumulated in Weekly Progress, weekly evaluations with presentations, and semester evaluations accumulated in Montessori Progress Reports. Keywords: Early Reading, Montessori Method, Early Childhood ABSTRAK Tujuan penelitian ini adalah untuk menganalisis dan mendeskripsikan (1) perencanaan pembelajaran Montessori dalam menstimulasi kemampuan membaca permulaan di Lovely Bee Montessori School Malang, (2) penerapan metode Montessori dalam menstimulasi kemampuan membaca permulaan anak usia dini di Lovely Bee Montessori School Malang, dan (3) evaluasi pembelajaran Montessori dalam menstimulasi kemampuan membaca permulaan anak usia dini di Lovely Bee Montessori School Malang. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara dengan kepala sekolah, guru kelas, dan tim Curriculum Department, kemudian melakukan observasi serta dokumentasi. Analisis data dilakukan dengan mereduksi data, memaparkan data, dan menarik kesimpulan. Pemeriksaan keabsahan data digunakan triangulasi teknik. Hasil penelitian menunjukkan bahwa: (1) perencanaan pembelajaran Montessori di Lovely Bee Montessori School Malang terdiri dari perencanaan tahunan berupa silabus dan Spider Web Montessori, perencanaan bulanan berupa Lesson Plan, dan perencanaan harian berupa Daily Lesson; (2) penerapan metode Montessori dalam menstimulasi kemampuan membaca permulaan anak usia dini di Lovely Bee Montessori School Malang dilaksanakan secara progresif dan bertahap melalui Pink Series, Green Series, dan Blue Series. Adapun karakteristik pembelajarannya adalah menggunakan pendekatan fonik (phonics approach), lingkungan dan bahan ajar yang dipersiapkan (prepared environment), dan belajar menulis sebelum membaca (writing before reading); (3) evaluasi pembelajaran Montessori terdiri dari evaluasi harian dengan observasi dan tes membaca yang diakumulasi dalam Weekly Progress, evaluasi mingguan dengan presentasi, dan evaluasi semester yang diakumulasi dalam Montessori Progress Report. Kata Kunci: Membaca Permulaan, Metode Montessori, Anak Usia Dini